2020
DOI: 10.1111/sifp.12136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Perceived Infertility in Ghana

Abstract: Perceived infertility is an understudied phenomenon in low‐ and middle‐income countries, where biomedical infertility can have severe consequences, particularly for women. We conducted a nationally representative survey of Ghanaian women, estimated the prevalence of and reasons for perceived infertility, and assessed factors associated with higher levels of perceived infertility using a partial proportional odds model. Among 4,070 women, 13 percent believed they were “very likely” to have difficulty getting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…We note that the prevalence of individuals perceiving a fertility problem may be underestimated because the question asks whether the perception of the respondent is based on medical advice, so it may have excluded individuals who perceived that they were infertile but who did not consult a physician. Moreover, because the question is rooted in medical diagnosis of difficulties conceiving, results may be less comparable to previous studies on perceived subfecundity based on survey questions that did not condition on medical advice (Gemmill 2018;Polis et al 2020;Polis and Zabin 2012;Passet-Wittig et al 2020;White et al 2006;Johnson et al 2020).…”
Section: Dependent Variablescontrasting
confidence: 59%
See 1 more Smart Citation
“…We note that the prevalence of individuals perceiving a fertility problem may be underestimated because the question asks whether the perception of the respondent is based on medical advice, so it may have excluded individuals who perceived that they were infertile but who did not consult a physician. Moreover, because the question is rooted in medical diagnosis of difficulties conceiving, results may be less comparable to previous studies on perceived subfecundity based on survey questions that did not condition on medical advice (Gemmill 2018;Polis et al 2020;Polis and Zabin 2012;Passet-Wittig et al 2020;White et al 2006;Johnson et al 2020).…”
Section: Dependent Variablescontrasting
confidence: 59%
“…Relationship status is an important situational factor that can also influence the ability to recognise the symptoms of infertility. Research has found that individuals are more likely to perceive difficulty in conceiving if they are in a union (Passet-Wittig et al 2020;Polis et al 2020;Gemmil and Cowan 2021) and that partnership stability and the partner's attitude toward childbearing can also affect people's ability to recognise the symptoms of infertility (Gemmil, Sedlander, and Bornstein 2021;Passet-Wittig et al 2020). These findings point to the inherently dyadic nature of the experience of infertility and confirm the importance of analysing subfecundity perceptions as a couple-level phenomenon.…”
Section: Previous Researchmentioning
confidence: 99%
“…Our survey design and sampling have been described in detail elsewhere. 42 Briefly, data for this analysis were drawn from a nationally representative, community-based survey of reproductiveaged (15-49 years) women in Ghana (N=4,722), conducted in 2018 as part of a larger study on abortion incidence in Ghana. 43 The survey was a collaborative effort between the Guttmacher Institute, the Kwame Nkrumah University of Science and Technology (KNUST), and the Performance Monitoring and Accountability 2020 team at the Johns Hopkins Bloomberg School of Public Health.…”
Section: Survey Design and Implementationmentioning
confidence: 99%
“…However, we argued in favor of the latter rather than for the former reasons, because other studies conducted in the same year as our study had reported a relatively poor instead of better inexpression of knowledge on the de nition of infertility. For example, in 2020, Polis et al reported that 66% of women in Ghana and 98% of women and men in Malawi expressed poor knowledge on infertility [19]. Furthermore, in 2021, a Nigerian study showed that approximately 51.3% of men expressed poor knowledge [20].…”
Section: Discussionmentioning
confidence: 99%